Cost-Effectiveness Of Drug Compliance In Type 2 Diabetes Mellitus Patients - Maciel, Olga; Vera, Zully; Marin, Gustavo H.; Morinigo, Macarena; Maidana, Mabel; Mastroianni, Patricia [UNESP] (Rjpbcs Research Journal Pharmaceutical, Biological & Chemical Sciences, 2018)
Type 2 diabetes mellitus affects 15% of the population around the world, causing health complications and increasing the treatment's costs. Being a chronic outpatient treatment disease, patient compliance is higher importance to achieve therapeutic success. The present study measure the cost effectiveness of the compliance of this disease. An observational, cross-sectional, pharmaco-economic study was performed. A National program to stimulate treatment adherence was taken as intervention stage. Compliance was measure by Morisky-Green test and details of the events in each patient's health (medication, consultations, hospitalization and concomitant treatments) were used to determinate the direct costs for Ministry of Public Health. Effectiveness was measured by percentage of glycated hemoglobin (HbA1c). The sample obtained was 55 patients, which were grouped into 31 compliant and 24 non-compliant. The cost-effectiveness of compliance was 466 US$ / compliant effective patient and 1,807 US$ / non-compliant effective patient. The cost-effectiveness of hypoglycemic drug therapy compliance is significantly lower (almost 4 times) than non-compliance. Type 2 Diabetes Mellitus patients that have no therapy adherence are not able to maintain protective levels of HbA1c. In addition, for the Ministry of Public Health, the lack of adherence requires more budget to accomplished the health goals.
Keywords: Cost-effectiveness; adherence; pharmacotherapy compliance; Type 2 Diabetes Mellitus